CONSTRUCTION AND VALIDATION OF A QUESTIONNAIRE FOR CARDIOPULMONARY RESUSCITATION KNOWLEDGE ASSESSMENT - Mateus Goulart Alves; Vanessa Oliveira Silva Pereira; Denise Ferreira Gomide Batista; Aldenora Laísa Paiva de Carvalho Cordeiro; Juliana da Silva Garcia Nascimento; Maria Célia Barcellos Dalri (Universidade Federal do Paraná, 2019)
Objective: To construct and validate a questionnaire related to adult cardiopulmonary resuscitation in Basic Life Support, using the Automatic External Defibrillator, in the hospital environment.Methodology: applied study, conducted at the University of São Paulo at Ribeirão Preto College of Nursing, from January 2017 to March 2018. Participants were 16 Urgency and Emergency experts, with Fehring's criteria used to select them. The rules of the National Council of Medical Examiners manual and guidelines of the American Heart Association were applied. Descriptive statistics and inter-rater agreement analysis through Gwet's AC1 were used. The questionnaire was validated in relation to organization, objectivity and clarity.Results: a validated questionnaire with 20 multiple choice questions with "almost perfect" inter-rater agreement was produced.Conclusion: the questionnaire was shown to be valid for use as an assessment instrument on the subject addressed.